Mombasa in the land and sea exchanges of East Africa - van Dongen, Irene S. (ERDKUNDE, 1963)
This paper examines the historical growth and expansion of Mombasa, which has long been a major seaport in East Africa. Particular emphasis is placed on the development of the port during the European rule in East Africa, which is now coming to an end. The three most important factors that have contributed to Mombasa’s remarkable development are: a) the location of the city, which offered particular advantages both for deep-sea navigation and for the city’s layout; b) the manner in which heavier goods were transported in East Africa and which resulted in the flow of trade being concentrated in Mombasa; c) the economic and social progress in the hinterland of Mombasa compared to the hinterland of other East African ports. Tables I and II show the distribution of East African trade by type and by commodity between Mombasa, Dares Salaam, Tanga, Lindi and Mtwara. Figure 3 shows the location of the origins of maritime trade in the hinterland. A separate section describes the port facilities currently available on Mombasa Island, at the Kilindini Terminus of the Deep Water Fairway and at the Port of Old Mombasa, which is still used by sailing vessels and some coastal vessels. It can be shown that the city of Mombasa expanded significantly in parallel with the increase in port throughput and that a differentiation in its functions has occurred compared to its original simple role of being the gateway to the East African Plateau. Over the decades, there have also been many changes in Mombasa’s overseas relations with the outside world, including coastal relations. There is no doubt that the so-called colonial period brought much prosperity to Mombasa. Of course, the question now arises as to what effect the forthcoming political changes will have on Mombasa, and what effect the construction of new railway lines, which is now underway, will have on the flow of East African trade to the port. Since Mombasa Island does not officially belong to the territory of Kenya, but to that part of the East African coast that is still under the Sultan of Zanzibar, the former ruler of East Africa, the possession of Mombasa itself is still the subject of negotiations between the independent East African states.